Unraveling Third Party Funding: ¿what is its role in investment arbitration? - Malpartida Zamora, Elody (2025)
Through “Third Party Funding,” a third party finances the costs of the arbitration process in exchange for a share of the case’s potential outcome. This article covers the historical background of Third Party Funding, its international regulation in investment arbitration, and its impact on the jurisdiction of arbitral tribunals and the admissibility of investment claims. It also addresses several ongoing debates, such as the risk of speculative or meritless cases being pursued, whether Third Party Funding agreements can influence decisions on arbitration costs, and whether the existence and/or terms of such agreements should be disclosed during the arbitral process.